Analisis Keterampilan Inovasi Produk Oleh Pelaku Usaha Kuliner Nagari Pasia Laweh Kecamatan Palupuh - Sukmawati, Renti; Rahmi, Rahmi (STAI Denpasar Bali, 2024)
One of the pillars of a region's economic strength is the Micro, Small and Medium Enterprises (MSME) sector. Seeing the phenomenon of MSME in Nagari Pasia Laweh which creates jobs and makes an important contribution to trade, especially for micro businesses operating in the culinary sector. In creating a good business, innovation is needed that can improve the performance of business actors, but there are still business actors who have not innovated their products. Culinary business actors who have innovated their products certainly experience several problems and obstacles. The aim of this research is to find out and analyze the product innovation skills of culinary business actors and to find out the obstacles or constraints in innovating culinary business products in Nagari Pasia Laweh, Palupuh District. The research method used is a qualitative descriptive method. Data obtained through observation, interviews and documentation. The results of this research are that 10 out of 12 business actors have carried out product innovations in the form of adding menu variants. The obstacles experienced during product innovation were 2 business actors being constrained by a lack of facilities and infrastructure, 3 business actors experiencing a lack of labor which resulted in a long time for the production process, 3 business actors being constrained by the distance to the location of purchasing complete raw materials and meat grinding for the actors. businesses that need it and 10 out of 12 business actors who have carried out product innovation are constrained by costs because they have to buy additional equipment and raw materials for the production process.